Pembatalan Perkawinan di Beberapa Negara Muslim Perbandingan Antara Maroko, Turki, dan Malaysia - Chabibatul Maulidah (Jurnal AL-AHKAM, 2023)
The purpose of this writing is to find out about matters relating to the cancellation of marriages in family law in several Muslim countries. Especially in Morocco, Türkiye and Malaysia. In this study the authors used descriptive comparative analysis method, namely describing and comparing several variables. Sources of data obtained in this study through literature studies. Based on the results of the research, the three countries have different mentions of marriage annulment, as well as different policies and laws. this is based on the background and needs of each country, legal renewal is also the cause of differences in the rules regarding the annulment of marriages.